2009
DOI: 10.1091/mbc.e09-01-0069
|View full text |Cite
|
Sign up to set email alerts
|

The Mating-specific Gα Interacts with a Kinesin-14 and Regulates Pheromone-induced Nuclear Migration in Budding Yeast

Abstract: As a budding yeast cell elongates toward its mating partner, cytoplasmic microtubules connect the nucleus to the cell cortex at the growth tip. The Kar3 kinesin-like motor protein is then thought to stimulate plus-end depolymerization of these microtubules, thus drawing the nucleus closer to the site where cell fusion and karyogamy will occur. Here, we show that pheromone stimulates a microtubule-independent interaction between Kar3 and the mating-specific Galpha protein Gpa1 and that Gpa1 affects both microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…The use of Gpa1 mutants indicated that Gpa1 affects positively the association of Kar3 to the shmoo tip as well as the dynamics and orientation of microtubules. These results suggest that Gpa1 serves as an externally regulated position determinant anchoring Kar3, a role not previously known for G␣ proteins (125). VOL.…”
Section: Pheromone Response and Nuclear Migrationmentioning
confidence: 60%
See 1 more Smart Citation
“…The use of Gpa1 mutants indicated that Gpa1 affects positively the association of Kar3 to the shmoo tip as well as the dynamics and orientation of microtubules. These results suggest that Gpa1 serves as an externally regulated position determinant anchoring Kar3, a role not previously known for G␣ proteins (125). VOL.…”
Section: Pheromone Response and Nuclear Migrationmentioning
confidence: 60%
“…In S. cerevisiae, it is reported that a mating-specific G␣, Gpa1, interacts with kinesin-14 (Kar-3), a minus-end-directed microtubule-associated motor, in a pheromone-responsive way (125). The interaction regulates pheromone-induced nuclear migration to the shmoo tip.…”
Section: Pheromone Response and Nuclear Migrationmentioning
confidence: 99%
“…In shmooing cells, cytoplasmic Kar3/Cik1 has been proposed to maintain depolymerizing MT plus ends at the shmoo tip (Meluh and Rose 1990;Maddox et al 2003). This is likely due to an interaction of Kar3 with the mating-specific Ga subunit of a trimeric G protein involved in pheromone signaling (Zaichick et al 2009). Pheromone stimulation increases the expression of KAR3 and CIK1 via activation of the transcription factors Ste12 and Kar4 (Kurihara et al 1996;Gammie et al 1999;Lahav et al 2007) and underlies the expression of the shorter NLS-less cytoplasmic Cik1 variant (Manning et al 1999;Benanti et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, further increases in the ratio of G proteins to receptors would be expected to lead to more complete suppression of the dominant-negative phenotype. However, it would be difficult to achieve such high levels without altering the balance of subunit biosynthesis or inducing secondary effects on the overall responses of the pheromone pathway arising from the multiplicity of roles of subunits (35,48,57).…”
Section: Fig 1 Cellular Level Of Expression Of Chromosomally Encoded mentioning
confidence: 99%